Insights into growth retardation and dwarfism caused by goose parvovirus in goslings: a transcriptomic profiling study - Zhang, Keshan; Gao, Guangliang; Chen, Zhuping; Zhang, Hongyuan; Zhao, Xianzhi; Li, Qin; Ma, Lin; Wang, Lecheng; Luo, Yi; Wang, Qigui (Frontiers in Veterinary Science, 2025)
Goose parvovirus (GPV) poses a significant threat to the waterfowl industry as it results in a high mortality rate and stunted growth in surviving goslings, leading to significant economic losses. We used 120 goslings and goose embryo fibroblasts inoculated with the GPV SYG61 strain to study the pathogenesis of GPV by pathological and gene expression profile changes. Fourteen days after infection with the GPV SYG61 strain, goslings showed a mortality rate of 63.33%, along with dwarfism, significant weight loss, and severe histopathological lesions in the liver and jejunum. Serum analysis revealed a marked increase in the levels of immunosuppressive factors such as TGF-β and IL-10 (p < 0.01 or p < 0.05), while the levels of pro-inflammatory cytokines such as IL-4, IFN-γ, TNF-α, and IgG remained unaffected. In addition, GPV infection inhibited the proliferation of goose embryo fibroblasts and induced apoptosis, as demonstrated by transcriptomic analysis, which identified 285 differentially expressed genes (DEGs). These DEGs were enriched in pathways involved in the negative regulation of cell proliferation (GO: 0008285, 19/276, LogP = −12.62) and skeletal system development (GO: 0001501, 25/227, LogP = −12.51), with key genes including IL6, CXCL8, PTGDS, PI15, MMP9, MMP13, MMP2, CCN3, and FAM180A. Other DEGs were linked to the IL-17 signaling pathway (hsa04657) and the regulation of programmed cell death (GO: 0043068). Notably, GPV infection activated both apoptosis and ferroptosis through the upregulation of key regulatory genes such as PTGS2, TF, and ASCL1 (p < 0.01). These findings indicated that GPV infection triggers inflammatory responses and programmed cell death, leading to high mortality in goslings, disturbs the expression of genes related to growth and skeletal development, and causes growth retardation and dwarfism in infected goslings. This study provides valuable insights into the pathogenic mechanisms of GPV and offers potential strategies to mitigate its impact and improve the productivity of the waterfowl industry.